DPD Performance Implementation in The Supervision Function Based on The Dignity of Justice - Wartoyo, FX; Prasetyo, Teguh (Balai Publikasi Indonesia, 2023)
The authority of the DPD is regulated in Article 22 D of the 1945 Republic of Indonesia Constitution which states that there are three functions of the DPD, namely the functions of legislation, consideration and supervision. However, these three functions are carried out by the DPD in a very limited manner. The existence of the DPR and the Supreme Audit Agency (BPK) as one of the state institutions is an implementation of the horizontal division of powers. The House of Representatives is an institution that has legislative, budgetary and supervisory functions, while the Supreme Audit Agency is an institution with the main function of auditing state finances. However, the supervisory function in regional budget matters carried out by the DPD is still part of the financial audit by the BPK. The principle that applies in state administrative law is that if an institution, including the DPD RI can measure performance, it means that the institution can know many things, such as being able to reward those who succeed, as well as being able to provide sanctions or recommend sanctions for those who fail; be able to know the actual cost; can link between costs and results; can determine whether it is better to do it yourself or need to outsource (outsourcing); can improve performance; can choose the best alternative